Effect of Torpor on Electrophoretic Spectrum of Bat Blood Immunoglobulins - Tovstukha , Igor; Ponomarenko , Oleksandr; Nahlov , Oleksandr (Problems of Cryobiology and Cryomedicine, 2020)
Probl Cryobiol Cryomed 2020; 30(3): 294